Learning Tools in Environmental Education at Fundación Niños de Los Andes in Manizales, Colombia - Flórez-Yepes, Gloria Yaneth (2018)
This article is part of the results of a research project whose objective was to formulate a strategy for environmental awareness for children and adolescents of the Fundación Niños de Los Andes (Children of the Andes Foundation) in the city of Manizales, Colombia. The methodological process was a quantitative and descriptive approach, using the survey as a tool for information gathering and the SPSS tool for systematization. A later discussion of the results was performed, and it determined the best way to approach the environmental education in children. The main conclusion was that the best strategy for acceptance of environmental education in children is to develop practical workshops that enable them to know, through real cases, environmental issues and ways of approach to prevent these issues, mitigate them, and control them.